2020
DOI: 10.3906/sag-1907-70
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic factors in bipolar disorders patients with manic episode

Abstract: Background/aim: Neurotrophins are one of the most important molecule groups affecting cerebral neuroplasticity. The amount of evidence about the role of changes in neuroplasticity in the pathophysiology of bipolar disease is growing. Materials and methods: We measured serum levels of brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), neurotrophin-3 (NT-3), glial cell-line derived neurotrophic factor (GDNF), vascular endothelial growth factor (VEGF), insulin-like growth factor-1 (IGF-1), fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Regarding treatment type, IGF-1 levels were not different between BD patients treated either with lithium or valproic acid ( Tuncel et al, 2020 ) or other drugs ( Kim et al, 2013 ). Notably, it has been shown in a lymphoblastoid cell line that the IGF-1 gene was overexpressed in BD-I patients who were lithium responders in contrast to both controls and non-responders ( Squassina et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding treatment type, IGF-1 levels were not different between BD patients treated either with lithium or valproic acid ( Tuncel et al, 2020 ) or other drugs ( Kim et al, 2013 ). Notably, it has been shown in a lymphoblastoid cell line that the IGF-1 gene was overexpressed in BD-I patients who were lithium responders in contrast to both controls and non-responders ( Squassina et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…IGF-1 gene expression was significantly decreased in the subependymal zone in BD patients ( Weissleder et al, 2021 ). Other studies evaluated the plasma levels of IGF-1 as a potential biomarker in BD patients ( Palomino et al, 2013 ; Kim et al, 2013 ; Liu et al, 2014 ; da Silva et al, 2017 ; Tuncel et al, 2020 ). One study conducted in Spain found that there was no significant difference in IGF-1 levels between first-psychotic episode BD patients and controls neither at baseline nor after 1, 6, and 12 months of treatment ( Palomino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to the best of our knowledge, there is no literature available on IGF-2 peripheral levels in major depressive disorders involving human samples. In contrast, peripheral IGF-1 has received far more attention in the last few decades, not just in depression [38][39][40][41][42][43][44][45][46][47][48][49], but also in other mental conditions such as schizophrenia [29,[49][50][51][52][53][54][55][56] and bipolar disorder [57][58][59][60][61][62]. On the other hand, circulating IGFBPs have been less widely studied than their ligand counterparts in the field of psychiatry, and always in a context of their IGF-dependent actions [29][30][31][32]38,55,[63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] NT-3 is known to play a role in developing several neuropsychiatric conditions such as bipolar disorder, schizophrenia, and depression. [ 4 , 6 , 8 ] NT-3 is considered a potential candidate gene in schizophrenia and reduced mRNA levels of NT-3 have been reported by earlier studies. [ 9 ] The NT-3 gene is positioned on chromosome 12p13.…”
Section: Introductionmentioning
confidence: 99%